Enhancement of p-nitrophenol adsorption capacity throughN2-thermal-based treatment of activated carbons - Álvarez-Torrellas, Silvia (2018)
In this work several activated carbons showing different textural and chemical properties were obtained by chemical and physical activation methods, using a lignocellulosic material (peach stones) as precursor. The activated carbon resulting from the chemical activation, namely as CAC, revealed the best textural properties (S BET = 1521 m 2 g −1 , pore volume = 0.90 cm 3 g −1 ) and an acidic character. It was found that the activated carbon obtained at 300 °C (under air atmosphere, PAC_air), and those synthesized at 750 °C in presence of N 2 flow with bubbling of water/12 M H 3 PO 4 solution (PAC_N 2 (H 2 O)/PAC_N 2 (H 3 PO 4 )), respectively, revealed worse textural properties, compared to CAC. Two functionalization treatments, by using sulphuric acid at boiling temperature (PACS) and nitric acid-urea-N 2 heating at 800 °C (PAC-NUT), were applied to PAC_air, in order to enhance the adsorption ability of the carbon material. Several techniques were carried out to characterize the physical and chemical properties of the obtained carbon materials. The modification treatments had influence on the carbon surface properties, since the nitric acid-urea-N 2 heating treatment led to a carbon material with highly-improved properties (S BET = 679 m 2 g −1 , pH IEP = 5.3). Accordingly, the original and modified-carbon materials were tested as adsorbents to remove 4-nitrophenol (4-NP), assessing batch and fixed-bed column adsorption tests. PAC-NUT carbon offered the best adsorption behavior (q e = 234 mg g −1 ), showing a high ability for the removal of 4-NP from water.